HUBUNGAN PENGETAHUAN TENTANG ANEMIA, DURASI TIDUR DAN KEBIASAAN SARAPAN DENGAN GEJALA ANEMIA PADA REMEJA PUTRI DI MAN 4 JAKARTA TAHUN 2022 - Rizka Rahma Aldila (2022)
Adolescent girls have a high risk of anemia. Anemia in adolescent girls can contribute to causing babies to be born with low birth weight (LBW), morbidity and mortality for both mother and baby. Lack of knowledge about anemia, lack of sleep duration, and the habit of skipping breakfast in adolescents are factors that cause anemia. The purpose of this study was to determine and analyze the relationship between knowledge about anemia, sleep duration, and breakfast habits with symptoms of anemia in adolescent girls at MAN 4 Jakarta in 2022. This study used a cross sectional study design with a quantitative approach. The sampling method used was stratified random sampling technique. The subjects in this study were adolescent girls aged 15-18 years, as many as 78 adolescent girls. Data on knowledge about anemia, sleep duration, breakfast habits, and anemia symptom status were taken using a questionnaire that was distributed directly in the form of a google form link. The results of the bivariate analysis using the chi-square test showed a relationship between knowledge about anemia (p = 0.001), sleep duration (p = 0.830), and breakfast habits (p = 0.017) with symptoms of anemia. This shows that there is a relationship between knowledge about anemia and breakfast habits with symptoms of anemia and there is no relationship between sleep duration and symptoms of anemia in adolescent girls at MAN 4 Jakarta in 2022.